POTENSI PERTUMBUHAN EKONOMI KOTA BITUNG - Jubert M. J. R. Suoth; Rine Kaunang; Lorraine W. TH. Sondak (Sam Ratulangi University, 2015)
Regional development is an integral part of national development one of benchmart for regional devel-opment is regional economic know previously the potential of a region that can be develop optimally. The asms of this study to determine the potential of the region has major effect of economic growth in Bitung cluring 2010 to 2013, and contribution of economic sector to economic growth in Bitung. This study used PDRB data Bitung City and North Sulawesi Province from 2010 to 2013. Data were obtained from the relevant agencies. Data ana-lyted using LQ analysis. The result showed that sector has LQ > 1 is processing Industry with average LQ 2,84 %, electricity, gas and pure water sector with average LQ 2,22 %, Transportasion and Communications sector with average LQ 1,82 % and Agriculture sector with average LQ 1,07 %. From the four sector showed that the four basic sector has economic strength and influence to increase economic growth in Bitung and this sector has been able to infest the needs of their own region. The industrial sector development as a basic sector, suggested to used local raw industrial, efficient and competitive and directed the development of Agriculture and fisheries industry, improving quality and economics product. The fourth development of the base sectors namely manufac-turing, electricity, gas and water supply, transport and communications and agriculture sector without neglecting the development of the non base which also has the potential for the sector is developed as the financial, real es-tate and business services sector and the services sector expected to be able to increase the rate of economic growth Bitung.Keywords: Potential Economic Growth